The Effect Of The Healthyqueen Website On The Improvement Of Adolescent Behavior About Menstruation - Tarissa Yunita Rahma; Evi Pratami; Rijanto; Ervi Husni; Wannarat Lawang (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Menstruation is bleeding in a manner periodic and cyclical from the accompanying uterus shedding of the endometrium. Cycle menstruation is time since day First menstruation until coming menstruation period next , meanwhile long cycle menstruation is distance between date started past menstruation and its start menstruation next . (Prayuni, Imandiri, & Adianti, 2018). This cycle can just variable , Symptoms menstruation also has impact strong negative on activity everyday and well-being , encouraging problem like poor mental health , decline productivity at work , and stress on the system health. Supported with results research conducted by Yilmaz, Bohara , and Thapa in 2021, 48% of sample report that they experience stress emotional during menstruation. The purpose of this study was to analyze the effect of the Healthyqueen website on increasing adolescent behavior regarding menstruation. This study use quantitative method pre - experimental research design with design One-group pretest-posttest design study. Sample taken with proportionate stratified random sampling technique of 52 respondents. The independent variable is the Healthyqueen website , while the dependent variable is level behavior adolecent about menstruation. Data collection instrument using questionnaire knowledge , attitude , action. Data analysis used is univariate and bivariate namely the Wilcoxon signed rank test with a significance level of 0.05. Research results show that there is enhancement significant behavior teenager daughter with p- value 0.000 <α (0.05) which means hipotesis accepted. The results of the study show the influence of the Healthyqueen website on increasing knowledge, attitudes and actions of adolescent about menstruation. Based on the description above, it can be concluded that there is an influence of the healthyqueen website on the behavior of young women. So it is recommended for adolescent to use the Healthyqueen website to find out and update related to menstruation